O aumentativo como expressão de hierarquia na língua tukano: uma análise semântico-pragmática - Antunes, Roger Alfredo de Marci Rodrigues (Universidade Federal de São Carlos, 2021)
This work aims to investigate the indexical anchorages that present social hierarchy in the Tukano language (ethnic and linguistic family from South America) regarding its pronominal use. It is well known that among various spheres of relations social hierarchies are somehow represented in the speech and are motivated in social groups by consanguineous, religious and financial relations. As far as indigenous languages are concerned, the Tukano language has been very productive in relation to the use of hierarchical markers, which differentiate from their conventional pronominal anchorages. It means that in the family contexts this language is rich in the representation of distance among their speakers. To carry out this research, interviews of native speakers of Tukano had been performed through the application of semi-directed investigation protocol. The questionnaires consisted of the validation of sentences created by linguists for the natives. Besides that and because it is a semantic-pragmatic analysis, being dependent on contextual options, it was also requested for the natives to select the most applicable sentence among many different situational contents. The analysis showed that in certain situations when Tukano speakers need to communicate, for instance as speaking to a superiorized subject, the augmentative morpheme occurs within their speech forms, according to this research’s initial hypothesis. A good example of this phenomenon is the sentence: mi’îhó yɨ’îre kumupatá mi'ĩtiasa’, that means “could big you bring the chair?” (here mi’î → you and -hó → the enhanced suffix) which would be used by a child or younger person to address his parent or an elderly within the family. This means different linguistic procedures are used depending on whether the speaker, in his speech context, addresses someone of the same level or a superior figure. To test that hypothesis various analyses had been carried out under two different but complementary fields. First, the Expressive Dimension (POTTS, 2005; 2007 and FORTIN, 2011) which allows to conclude that this morpheme works on a temporal degree, not only on a spatial degree, as the augmentative morpheme is used to be represented. Secondly, the Honorification (LEVINSON, 2007 [1983]) that permits to define the phenomenon through the point of view of pragmatics. This work intends to contribute to the study of representation of the social hierarchy of Tukano individuals as an universal element in natural languages within both fields of Pragmatics and Semantics. Furthermore, it will hopefully bring more attention to the Tukano language and to contribute to its revitalization.
The augmentative as an expression of hierarchy in the tukano language: a semantic-pragmatic analysis
Keywords: Análise semântico-pragmática; Língua tukano; Dimensão expressiva; Honoríficos; Aumentativo; Semantic-pragmatic analysis; Tukano language; Expressive dimension; Honorifics; Augmentative; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA